2021
DOI: 10.1183/13993003.00002-2021
|View full text |Cite
|
Sign up to set email alerts
|

Dyspnoea and respiratory muscle ultrasound to predict extubation failure

Abstract: This study investigated dyspnea intensity and respiratory muscles ultrasound early after extubation to predict extubation failure.It was conducted prospectively in two intensive care units in France and Canada. Patients intubated for at least 48 h were studied within 2 h after an extubation following a successful spontaneous breathing trial. Dyspnea was evaluated by the Dyspnea-Visual Analog Scale from 0 to 10 cm (VAS) and the Intensive Care - Respiratory Distress Observational Scale (range 0–10). The ultrasou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 49 publications
0
33
0
1
Order By: Relevance
“…Our study has limitations: The post hoc nature of these analyses and the small sample make the results hypothesis generating, warranting further confirmatory investigations; the thresholds proposed should be taken cautiously; and VAS dyspnea is mainly used to compare dyspnea within a subject before and after a stimulus is applied, but it has been recently used to compare subjects undergoing noninvasive support ( 4 , 5 ). We believe that its application in the present investigation is legitimate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study has limitations: The post hoc nature of these analyses and the small sample make the results hypothesis generating, warranting further confirmatory investigations; the thresholds proposed should be taken cautiously; and VAS dyspnea is mainly used to compare dyspnea within a subject before and after a stimulus is applied, but it has been recently used to compare subjects undergoing noninvasive support ( 4 , 5 ). We believe that its application in the present investigation is legitimate.…”
Section: Discussionmentioning
confidence: 99%
“…Pa O 2 /F i O 2 , Pa CO 2 , and VAS dyspnea were measured while patients were receiving Venturimask oxygen before randomization. VAS dyspnea was assessed by visual analog scale, ranging from 0 to 10, with 10 representing the worst symptom ( 4 , 5 ). For patients with VAS dyspnea = 0, Pa O 2 /(F i O 2 × VAS dyspnea) was considered equal to Pa O 2 /F i O 2 .…”
Section: Methodsmentioning
confidence: 99%
“… 14 Patients with respiratory muscle dysfunction cannot generate adequate strength to drive ventilation and often have lower V T , which causes more dyspnea and unstable V T during exercise. 16 Therefore, when respiratory muscle weakness develops, symptoms progress to dyspnea, tachypnea, and paradoxical respiration. 17 We found that the decrease in the MIP of patients who underwent lobectomy was greater than that of patients who underwent wedge resection, which is consistent with the reduction in V T during exercise in patients who underwent lobectomy.…”
Section: Discussionmentioning
confidence: 99%
“…This can typically result from an unfavorable respiratory system load-capacity balance, as it occurs in cases of SBT failure [ 10 ]. The association between dyspnea and SBT failure has indeed been reported [ 11 15 ], as well as post-extubation dyspnea is predictive of extubation failure [ 16 ].…”
Section: Introductionmentioning
confidence: 98%